2022
DOI: 10.31234/osf.io/jfqbg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-Term Dynamics of Pride and State Self-Esteem Change During the University-to-Work Transition

Abstract: Young adults differ in their self-esteem change during the university-to-work transition. The short-term processes related to individual variability in change are not yet fully understood. We examined experiences of pride in daily life as a dynamic process underlying self-esteem change. We followed 238 Dutch master students over 8 months across their university-to-work transition. We used dynamic and multilevel structural equation models to analyze three waves of 14-day experience sampling data. We first exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Our lab has conducted such studies (GradLife: job entry; STRIDE: educational transition; NiMO: motherhood). For job entry, we found dynamic links between daily mastery and personality states (Reitz et al, 2022a) and between pride and self-esteem across days and co-development across the transition (Diwan et al, 2023).…”
Section: Methodologies Suited To Capture the Individual Experience Of...mentioning
confidence: 91%
“…Our lab has conducted such studies (GradLife: job entry; STRIDE: educational transition; NiMO: motherhood). For job entry, we found dynamic links between daily mastery and personality states (Reitz et al, 2022a) and between pride and self-esteem across days and co-development across the transition (Diwan et al, 2023).…”
Section: Methodologies Suited To Capture the Individual Experience Of...mentioning
confidence: 91%
“…The lack of knowledge about within-day effect sizes from previous research and the complexity of the experience sampling data and multilevel analyses with many parameters complicated a priori power analyses for our specific research questions. However, a previous experience sampling study using the same dataset found enough power to detect small prospective associations for more well-studied momentary constructs such as positive affect (Diwan et al, 2023).…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Trait Self-Esteem as Moderator of the Social Interactions-Self-Esteem Association Considerable individual differences have been found in daily self-esteem processes in previous studies (Denissen et al, 2008;Diwan et al, 2023). Therefore, we aimed to further explore the role of individual differences in the self-esteem-social interactions links.…”
Section: Morning Self-esteem and Anticipated Social Interactions Duri...mentioning
confidence: 93%
See 1 more Smart Citation